In-silico design and experimental validation of TiNbTaZrMoSn to assess accuracy of mechanical and biocompatibility predictive models. (December 2021) - Torres-Sanchez, C.; Alabort, E.; Wang, J.; Norrito, M.; Conway, P.P.
Abstract: Numerical design of TiNbTaZrMoSn alloy preceded its manufacture and mechanical, physico-chemical and in vitro characterisation. The specifications of the alloy required a multi-objective optimisation including lower modulus of elasticity than c.p.Ti, high strength, stabilised β crystal structure with a low martensitic start temperature, a narrow solidification range and high biocompatibility. The results reveal that there was a good match between the bulk mechanical properties exhibited by the alloy experimentally and those predicted. Regarding surface properties, independent of roughness effects, the oxide thickness and surface zeta-potential, measured in biologically relevant electrolytes and at physiological pH, arose as important factors in osteoblastic activity (i.e., cell proliferation, measured via DNA, protein and metabolite content, and differentiation, via ALP levels), but not in cell adhesion and viability. The thinner oxide layer and lower absolute value of surface zeta-potential on the TiNbTaZrMoSn alloy explain its lesser osteogenic properties (i.e., inhibition of ALP activity) compared to the c.p. Ti. This study demonstrates that the numerical models to predict microstructure and bulk mechanical properties of β-Ti alloys are robust, but that the prediction of cellular bioactivity lags behind and still requires parameterisation to account for features such as oxide layer composition and thickness, electro-chemical properties and surface charge, and topography to optimise cell response in silico before committing to the costly manufacture and deployment of these alloys in regenerative medicine. Graphical abstract: Image 1 Highlights: Multiobjective optimisation included thermo-mechanical, -dynamic stability and biocompatibility. Optimal alloy designed was Ti-27.5Nb-8.5Ta-2.5Zr-3.5Mo-4.5Sn (wt. %). Elemental partitioning in inter-/dendrites was simulated and matched experimental measurements. Surface oxide layer in the alloy was less rich in TiO2, less electronegative and thinner than cpTi. Alloy supports proliferation but differentiation was retarded compared to cpTi.